Restorative Justice Approach in Resolving Corruption Cases Based on State Financial Loss Recovery in Indonesia - Setyawan, Donny Haryono; Iyah Faniyah; Otong Rosadi (Ekasakti Journal of Law and Justice, 2024)
Efforts to recover state losses due to corruption are carried out through additional criminal payments as stipulated in Article 18 of Law Number 31 of 1999 concerning the Eradication of Corruption as amended by Law Number 20 of 2001. These efforts have not succeeded and have given rise to other problems in law enforcement, namely arrears in substitute money, budget inefficiencies, and overcapacity in prisons. Therefore, other methods are needed as alternatives in dealing with corruption. This research study is about optimizing the recovery of state financial losses due to corruption crimes carried out with a restorative justice approach and the existence of restorative justice in corruption crimes based on state financial recovery. The specification of this study is descriptive analytical, with a normative juridical approach supported by an empirical juridical approach. Based on the results of the study, restorative justice is optimal in recovering state financial losses and community losses, because recovery of state financial losses or community losses is a condition for solving corruption crimes with a restorative justice approach. This optimization causes the resolution of corruption crimes using a restorative justice approach to be more effective in preventing arrears of new substitute money than if cases were resolved through the courts, effective in overcoming the problem of budget inefficiencies in handling corruption cases with small losses, and effective in preventing the addition of new prisoners / prisoners in prisons that are already overcapacity. The existence of restorative justice in corruption crimes based on the recovery of state financial losses is only limited to policies that are at the stage before the investigation or pre-investigation. The settlement is in the form of a decision whether an investigation is carried out on a corruption report or not. The decision to be taken depends on the factor whether loss recovery has been made or not. If the loss has been recovered then the report is not continued to the investigation, otherwise if the loss is not recovered then an investigation is carried out (ultimum remedium).